Smart Turn Signal for Autos and Motorcycle / Muhammad Zamri Ramli and Saiful Hafiz Juhari - Ramli, Muhammad Zamri; Juhari, Saiful Hafiz (2000)
Smart Turn Signal for Autos and Motorcycle is a simple circuit that produces a signal of lamp. It is important to vehicles industries. This circuit is design to give an easy work to consumer when they drive vehicles on the road. The main part of the circuit is 9v - voltage supply, transistor MOSFETs, variable resistors and IC 555. Today, the vehicles industry is no longer using this circuit They modified the circuit, not using component electronic but connected to coil and depend on battery. However, this circuit can also be applied for other applications.